2013
DOI: 10.5534/wjmh.2013.31.2.126
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Testosterone Deficiency and Men's Health

Abstract: Testosterone is important in the physiology of various organs and tissues. The serum testosterone concentration gradually declines as one of the processes of aging. Thus, the concept of late-onset hypogonadism has gained increasing attention in the last few years. Reported symptoms of late-onset hypogonadism are easily recognized and include diminished sexual desire and erectile quality, particularly in nocturnal erections, changes in mood with concomitant decreases in intellectual activity and spatial orienta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(56 citation statements)
references
References 98 publications
(93 reference statements)
2
52
0
2
Order By: Relevance
“…In addition, studies indicate that a state of testosterone deficiency could impair glucose homeostasis and insulin signaling, leading to the development of obesity, insulin resistance, and type 2 diabetes mellitus (Grossmann et al 2009). Several studies have also demonstrated that a testosterone-deficient condition causes osteopenia and osteoporosis (Dupree & Dobs 2004, Tsujimura 2013). However, the effects of combined testosterone deprivation and obese insulin resistance on bone morphology, osteoblastic insulin signaling and cell survival have not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, studies indicate that a state of testosterone deficiency could impair glucose homeostasis and insulin signaling, leading to the development of obesity, insulin resistance, and type 2 diabetes mellitus (Grossmann et al 2009). Several studies have also demonstrated that a testosterone-deficient condition causes osteopenia and osteoporosis (Dupree & Dobs 2004, Tsujimura 2013). However, the effects of combined testosterone deprivation and obese insulin resistance on bone morphology, osteoblastic insulin signaling and cell survival have not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…38 Recent large-scale cohort analyses have associated low testosterone levels with coronary artery diseases. 39,40 A more recent study of 308 men with ED showed that low testosterone levels were associated with an increased risk of CVD and that high testosterone levels could decrease this risk. 41 Previous studies have shown that EST parameters are not correlated with total testosterone and steroid hormone levels.…”
Section: Discussionmentioning
confidence: 99%
“…However, sex-specific associations of soy foods with cardiometabolic health, with favorable effects in women and unfavorable effects in men, have been reported in a number of studies [31,32] . Other reported male-specific adverse effects of soy consumption include fibrinolysis, coagulation and lower serum testosterone levels [33][34][35][36] , and the latter has been previously associated with an increased risk of DM and metabolic syndrome [34,37,38] . Furthermore, compared with females, male subjects tended to be more likely to be smokers, and consumed more alcohol and red meats, which may diminish the benefit of soy foods consumption.…”
Section: Discussionmentioning
confidence: 99%